Enhancing canola breeding by editing a glucosinolate transporter gene lacking natural variation. Issue 4 (25th January 2022) - He, Yizhou; Yang, Zhiquan; Tang, Minqiang; Yang, Qing-Yong; Zhang, Yuanyuan; Liu, Shengyi
Abstract : A low seed glucosinolate resource was developed in polyploid B. napus using a method that identifies the functions of genes with rare or no genetic variation.